Catalytic activity of poly(N-vinylpyrrolidone) protected gold nanoparticles deposited on ZnO (International Journal of Biology and Chemistry, 2014)
Gold (AuNPs) nanoparticles protected by poly(N-vinylpyrrolidone) (PVP) were prepared by «one-pot» synthetic protocol. Absorption spectra, size, morphology, structure and thermal properties of AuNPs were studied by UV-Vis spectroscopy, DLS, TEM and SAXS. According to DLS and SAXS measurement the average size of AuNPs stabilized by PVP in aqueous solution is varied from 6 to 15 nm. PVP protected AuNPs were deposited on zinc oxide by impregnation method. TEM images reveal that the average size of AuNPs-PVP deposited on the surface of ZnO is arranged between 6 and 10 nm and coincides well with DLS and SAXS measurements. The catalytic activity of polymer-protected AuNPs supported on the surface of ZnO was evaluated with respect to decomposition of hydrogen peroxide. The optimal conditions H2O2 decomposition in dependence of catalysts amount, concentration of substrate and temperature was found.